A influência da cepa de levedura e o uso da glutationa como antioxidante em vinhos sauvignon blanc - Antunes, Ingrid da Chaga (2017)
In the Gaúcha Campaign the production of grapes began in punctual areas with the Jesuits in the XVII and with the Portuguese in the XVIII. The region is located in the 31° parallel, which identifies other regions producing wines of reputation and of the highest quality. The cultivar Sauvignon Blanc is one of the most important white vines. In Rio Grande do Sul it is cultivated on a small scale. Originally from Bordeaux or the Loire Valley, France. Antioxidants are molecules capable of acting against the normal damages caused by the physiological process of oxidation, in that they are able to delay or prevent oxidative damages. Glutathione is a natural antioxidant, constituent of grapes. Due to the complexity and variability of its behavior, the evolution of glutathione during vinification can change dramatically and the concentration can be manipulated by the oenologist, limiting the oxidation throughout the process of vinification and aging of the wines. Selected in the active dry form, the addition of selected yeasts to the must is a widespread practice in the elaboration of white wine. The objective of the present work is to evaluate the use of different strains of yeasts in Sauvignon Blanc wines, as well as the use of glutathione as antioxidant of white wine in the region of the Rio Grande do Sul Campaign. The experiment was carried out at the experimental winery of the Federal University of Pampa - UNIPAMPA Campus Dom Pedrito, Dom Pedrito, RS. To elaborate the work, 171 kg of grapes of the cultivar Vitis vinifera Sauvignon Blanc were used. The Sauvignon Blanc wines that had the addition of glutathione in the prepackage, did not show significant differences in relation to the wines that had addition of SO2, also in the prepackage. Given this, it is clear the possibility of using both one and the other in the pre-packaging stage as antioxidants of white wines. Zymaflore X5® yeast had a higher alcohol content when compared to Maurivim PDM and AWRI 796, where the lowest was from AWRI 796. The yeast AWRI 796 had a higher concentration of reducing sugars, while Maurivin PDM had the lowest concentration. The yeast AWRI 796 presented higher concentration of dry extract. Sauvignon Blanc wines made with different types of yeasts did not show significant differences for the variables tonality and color intensity. As well as for the values of pH, Volatile Acidity, Ashes and Dry Extract. Zymaflore X5® showed higher fermentation capacity, obtaining a higher alcohol content and lower sugar content in relation to the others studied. While yeast AWRI 796 showed the lowest alcoholic strength and consequently higher residual sugar content.